Analisis Perilaku Wanita Dengan IVA (Inspeksi Visual Asam Asetat) Positif Dalam Lanjutan Pemeriksaan Deteksi KankerServiks - Dhea Adellina Riyadi; Riri Maharani; Risa Amalia (Jurnal Kesehatan Komunitas, 2020)
A reproductive health problem faced by women presents an increase in infections of the reproductive organ’s sequel will cause cancer, one of them is cervical cancer. Cervical cancer is a primary tumor strike the organs of the female reproductive, between themselves and the uterus. The purpose of this is to analyze the research behavior of women visual inspection with acetic acid (VIA) positive in advanced examination detection of cervical cancer. Data in this study was obtained through observation and in-depth interviews of as many as 11 informants where there are the main informants, 5 informans advocates, and 1 key informant. The data validity used triangulation method. Data analyzed by content analysis. The results of observation and interview showed that there was low knowledge and attitudes of women with VIA positive because of their education background were elementary and junior high school, while knowledge is a basic of further examination. Information obtained through print media, and electronic media. Health workers were conducted counseling mobile VIA and cilical breast examination. Women with VIA positive is unwilling to conduct the advanced examination, fear, because of stress, shame, and less comfortable and poor awareness of the importance of advanced examination. Family encouragement doesn't obtain because women VIA positive checked, without the knowledge of the family while the family is the part most important give support to conducts the advanced examination. A reproductive health problem faced by women presents an increase in infections of the reproductive organ’s sequel will cause cancer, one of them is cervical cancer. Cervical cancer is a primary tumor strike the organs of the female reproductive, between themselves and the uterus. The purpose of this is to analyze the research behavior of women visual inspection with acetic acid (VIA) positive in advanced examination detection of cervical cancer. Data in this study was obtained through observation and in-depth interviews of as many as 11 informants where there are the main informants, 5 informans advocates, and 1 key informant. The data validity used triangulation method. Data analyzed by content analysis. The results of observation and interview showed that there was low knowledge and attitudes of women with VIA positive because of their education background were elementary and junior high school, while knowledge is a basic of further examination. Information obtained through print media, and electronic media. Health workers were conducted counseling mobile VIA and cilical breast examination. Women with VIA positive is unwilling to conduct the advanced examination, fear, because of stress, shame, and less comfortable and poor awareness of the importance of advanced examination. Family encouragement doesn't obtain because women VIA positive checked, without the knowledge of the family while the family is the part most important give support to conducts the advanced examination.